Kajian Teknis Penanganan Longsoran Sta. 2+850 - 3+050 pada Pembangunan Jalan Tol Balikpapan Samarinda Menggunakan Bored Pile Metode Plaxis - Juandra Hartono (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
Construction of the Balikpapan - Samarinda toll road through hilly areas and valley or basin areas. At Sta. 2 + 850 to Sta. 3 + 050 passing through the area it is necessary to reach the finished class required a high level of landfill. Embankment on the Balikpapan - Samarinda toll road construction project has been carried out, but the results are less than perfect so that there is currently damage to the area. Damage that occurred in the form of sinkhole, cracked soil and landslides in the original soil layer / base deep enough to cause the structure of the box culvert that stands on it damaged (box culvert broken and shifted). To improve and to ensure the stability of the structure in the future (box culvert and high landfill), it is necessary to do geotechnical engineering in the form of slope reinforcement technology using reinforcement material (borepile) that is plugged into the ground until it passes through the skid. Technical review of landslides handling at Sta. 2 + 850 to Sta. 3 + 050 using existing soil parameters and modeling using the plaxis program version 8.20. The result of the calculation of landslide handling before the alternative treatment is obtained the total displacement is 0.109 m and SF = 1.139, this shows that the pile of work in the field is still quite critical in terms of design. When reinforced with borepile (either single or double borepile) placed on the berm section obtained a safe number of SF = 1.779 (single) and SF = 1.796 (double), this shows that the number of bored piles is insignificant and the reinforcement is very effective or useful if placed in the berm section. Based on the safe figures obtained, the landslide handling solution uses doubel borepile.